Waqf Land Certification Postponement for Place of Worship Due to the Obscurity of the Toll Road Expansion Project (Re-overview of Gustav Radbruch's Three Basic Legal Values Theory) - Zidney Ilma Fazaada Emha; Ana Silviana; Musahadi Musahadi (Al-Ahkam, 2022)
Data from the Ministry of ATR/BPN shows that most waqf lands have legal certainty problems. This article wants to look at the case of delaying the certification of waqf land for the Baitussalam Mosque in Semarang City due to the unclear toll road expansion project. The discussion is related to Gustav Radbruch's theory of three fundamental legal values. This paper uses an empirical juridical approach with a qualitative descriptive-analytical research specification. Data were obtained through interviews with several key informants and supported by legal materials obtained from literature studies. The results showed that the delay in certifying the waqf land of Baitussalam Mosque at the Semarang City Land Office was due to legal concerns by residents if the land was affected by the expansion of the toll road project. This article proves that Gustav Radbruch's standard priority teachings, which prioritize justice over expediency and legal certainty, are irrelevant and not ideal. The case of Baitussalam Mosque places legal certainty through waqf land certification as a top priority that must be carried out. Thus, this study confirms the teaching of casuistic priority in the theory of modern legal goals.